Additive-free photo-mediated oxidative cyclization of pyridinium acylhydrazones to 1, 3, 4-oxadiazoles: solid-state conversion in a microporous organic polymer and supramolecular energy-level engineering. Issue 4 (7th January 2021) - Kim, Kyung-su; Chung, You Kyoung; Kim, Hyunwoo; Ha, Chae Yeon; Huh, Joonsuk; Song, Changsik
Abstract : We discovered the efficient catalyst-free, photo-mediated oxidative cyclization reaction of bis- p -pyridinium benzoyl hydrazone (BH1 ) to 2-pyridinium-5-phenyl-1, 3, 4-oxadiazoles. Abstract : We discovered the efficient catalyst-free, photo-mediated oxidative cyclization reaction of bis- p -pyridinium benzoyl hydrazone (BH1 ) to 2-pyridinium-5-phenyl-1, 3, 4-oxadiazoles. This photoreaction is remarkable because it does not require additives ( e.g., bases, strong oxidants, or photocatalysts), which are essential in previous reports, and proceeds very effectively even with solid-state microporous organic polymers. Interestingly, we found that the inclusion complexation of BH1 with cucurbit[7]uril (CB7 ) interferes with the photo-induced electron transfer from BH1 to molecular oxygen through modification of the LUMO energy level, thus inhibiting the photo-medicated oxidative cyclization.